Synthesis and Characterization of Cetyl Piridinium Chloride Modified and Al2O3 Pillared Clay - ferry arifiadi; Irna Rosmayanti; Herlina Damayanti; Hernawan Hernawan; Kristanto Wahyudi (Balai Besar Keramik, 2020)
Bentonite is a mineral that is very abundant in Indonesia and has the potential to be developed, one of which is by adding intercalant to obtain a modified bentonite with the desired characteristics. In this study, the synthesis was carried out by the intercalation method by surfactant Cetyl pyridinium Chloride (CPC) with % weight variations and then followed by pillarization with aluminum polyoxo. Then the resulting solid phase is calcined at a temperature of 450oC. The results obtained were that bentonite with modified CPC and aluminum polyoxo had higher basal distance and surface area characteristics compared to natural bentonite and this increase was also proportional to the amount of CPC added before the pillarization process. The best modification value in the addition of CPC was 36% by weight with a basal distance of 16,8898 Å and a surface area of 276.478 m2 / g. From this research, it can be concluded that the addition of CPC and aluminum polyoxo to bentonite can increase the basal distance and its surface area. The added CPC concentration also has an effect on increasing the number of pillar cations that enter the bentonite so that the pillarization that occurs in bentonite is more and causes the characteristics of the bentonite to be better.